The Contributions of Frank Moore Cross to Semitic and Hebrew Philology - Huehnergard, John (Bulletin of ASOR, 2014)
Frank Moore Cross's contributions to Semitic and Hebrew philology were both direct and indirect: direct, in his publications on aspects of Hebrew, Phoenician, and Aramaic grammar; and indirect, in his insistence on the rigorous use of philological method in the study of ancient texts, whether those were Ugaritic inscriptions, or Aramaic papyri, or the Hebrew Bible. The application of historical and comparative Semitic linguistics not only pervades his many publications, but was something that Cross taught his students to apply in their research as well. While Cross was better known for his contributions to biblical history, epigraphy, and Qumran studies, his deep knowledge of Semitic philology, and his meticulous use of it in his research, also marked him as one of the foremost philologists of the 20th century.